Pseudomonas aeruginosa Infection Modulates the Immune Response and Increases Mice Resistance to Cryptococcus gattii - Peres-Emidio, Eluzia C.; Freitas, Gustavo J. C.; Costa, Marliete C.; Gouveia-Eufrasio, Ludmila; Silva, Lívia M. V.; Santos, Anderson P. N.; Carmo, Paulo H. F.; Brito, Camila B.; Arifa, Raquel D. N.; Bastos, Rafael W.; Ribeiro, Noelly Q.; Oliveira, Lorena V. N.; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Cryptococcosis is an invasive mycosis caused by Cryptococcus spp. that affects the lungs and the central nervous system (CNS). Due to the severity of the disease, it may occur concomitantly with other pathogens, as a coinfection. Pseudomonas aeruginosa (Pa), an opportunistic pathogen, is also able to cause pneumonia. In this work, we studied the interaction of C. gattii (Cg) and Pa, both in vitro and in vivo. Pa reduced growth of Cg by the secretion of inhibitory molecules in vitro. Macrophages previously stimulated with Pa presented increased fungicidal activity. In vivo, previous Pa infection reduced morbidity and delayed the lethality due to cryptococcosis. This phenotype was correlated with the decreased fungal load in the lungs and brain, showing a delay of Cg translocation to the CNS. Also, there was increased production of IL-1β, CXCL-1, and IL-10, together with the influx of iNOS-positive macrophages and neutrophils to the lungs. Altogether, Pa turned the lung into a hostile environment to the growth of a secondary pathogen, making it difficult for the fungus to translocate to the CNS. Further, iNOS inhibition reverted the Pa protective phenotype, proving its important role in the coinfection. Altogether, the primary Pa infection leads to balanced pro-inflammatory and anti-inflammatory responses during Cg infection. This response provided better control of cryptococcosis and was decisive for the mild evolution of the disease and prolonged survival of coinfected mice in a mechanism dependent on iNOS.